2014
DOI: 10.1007/s12665-014-3671-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of water-extractable fractions from South Moravian lignite

Abstract: International audienceLignite can be applied directly in natural form on agricultural fields as a soil conditioner. However, there is little information on leaching of risky compounds by its interaction with water. South Moravian lignite was therefore extracted with water at 25 A degrees C and 2.3 % of water-soluble fractions were obtained from lignite corresponding to 0.3 % of total organic carbon. All ten fractions form aromatic and aliphatic structures with oxygen-containing functional groups such as carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 60 publications
(72 reference statements)
0
16
0
Order By: Relevance
“…that degrade lignin in wood waste can enhance the degradation of persistent organic pollutants such as pentachlorophenol (Mileski et al, 1988). Microbial inhibition in biosolids caused by poor aeration, low pH, or high concentrations of metals may be reduced by mixing the biosolids n/g (Paramashivam et al, 2016b), (Wilén et al, 2004) Pine ( (12) 55 (12) (Enders et al, 2012), (Pereira Calvelo et al, 2011), (Hina et al, 2010) n/a n/a n/a n/a (Zhang et al, 2015) 600 9.6 37.1 0.4 n/a n/a 42.6 n/a n/a n/a n/a Lignite New Vale, New Zealand with organic amendments (Song and Schobert, 1996;Pehlivan and Arslan, 2007;Chassapis et al, 2009;Knowles et al, 2011;Simmler et al, 2013;Doskocil et al, 2015). Xenobiotics can be immobilized or entrapped within the micropores of organic soil amendment (Fetzner, 2000).…”
Section: Sorption Of Xenobiotics and Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…that degrade lignin in wood waste can enhance the degradation of persistent organic pollutants such as pentachlorophenol (Mileski et al, 1988). Microbial inhibition in biosolids caused by poor aeration, low pH, or high concentrations of metals may be reduced by mixing the biosolids n/g (Paramashivam et al, 2016b), (Wilén et al, 2004) Pine ( (12) 55 (12) (Enders et al, 2012), (Pereira Calvelo et al, 2011), (Hina et al, 2010) n/a n/a n/a n/a (Zhang et al, 2015) 600 9.6 37.1 0.4 n/a n/a 42.6 n/a n/a n/a n/a Lignite New Vale, New Zealand with organic amendments (Song and Schobert, 1996;Pehlivan and Arslan, 2007;Chassapis et al, 2009;Knowles et al, 2011;Simmler et al, 2013;Doskocil et al, 2015). Xenobiotics can be immobilized or entrapped within the micropores of organic soil amendment (Fetzner, 2000).…”
Section: Sorption Of Xenobiotics and Heavy Metalsmentioning
confidence: 99%
“…that degrade lignin in wood waste can enhance the degradation of persistent organic pollutants such as pentachlorophenol (Mileski et al, 1988). Microbial inhibition in biosolids caused by poor aeration, low pH, or high concentrations of metals may be reduced by mixing the biosolids with organic amendments (Song and Schobert, 1996; Pehlivan and Arslan, 2007; Chassapis et al, 2009; Knowles et al, 2011; Simmler et al, 2013; Doskocil et al, 2015).…”
Section: Sorption Of Xenobiotics and Heavy Metalsmentioning
confidence: 99%
“…The most commonly used sorbent for this purpose is active carbon, nevertheless, this detoxification strategy suffers from high cost of the sorbent [ 6 ]. On the contrary, lignite represents a very promising, low-cost, and effective sorbent which has already been used for the treatment of wastewater to remove various organic and inorganic contaminants [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extracted component of the coal sample was influenced by the extraction solvent. Dosko cil [51] studied the water-extractable fractions from South Moravian lignite, and results showed that the main contents of the off-line TMAH thermochemolysis of lignite were aromatic compounds (77% of the total identified molecules), such as benzene carboxylic acids and their derivatives, especially methoxybenzoic acids, and to a lesser extent, methoxybenzenes. The identified aliphatic compounds consisted of short-chain diacids, fatty acids and polyols and were 23% of the identified compounds.…”
Section: Coalmentioning
confidence: 99%